Stepping in, aside or away? A micro-level study of commitment in cross sector partnerships - Sehgal, Sarita Danute (Graduate School of Business (GSB), 2023)
Cross sector partnerships (CSPs) are considered essential for addressing grand challenges, yet the actual partnering process often leads to friction, disappointing results, and dismay for those involved. Scholars have identified that individuals play a critical role in the success of cross sector collaboration and that their commitment to the partnership facilitates CSP functioning. However, the micro-level aspects of commitment within CSPs have yet to be examined carefully. The partnership literature calls for more in-depth research on individuals and recommends drawing from the fields of organizational behaviour and organizational psychology. Meanwhile, the commitment literature calls for examination of workplace commitment within cross boundary settings and in relation to higher purpose causes. My interpretive, micro-level study responds to these parallel and synergistic needs for additional research by exploring what shapes individuals' commitment to cross sector partnerships. I use a constructivist grounded theory approach to conduct a longitudinal, comparative case study of 23 health partnership practitioners in South Africa. My findings are consolidated in an empirically developed model that describes how the nature of individuals' CSP commitment differs depending on which of three key commitment targets (employing organization, career, or social goal) they prioritize in the context of the partnership. In distinguishing between those who are instrumentally vs altruistically committed to the CSP, the model outlines two pathways through adversity which result in four different behavioural outcomes of exiting, stepping aside, stepping away or stepping in. Critically, the model illustrates what enables certain partnership practitioners to sustain CSP commitment despite adversity and how eudaimonic well-being is generated through this process. My examination of workplace commitment within CSPs contributes to the partnership literature by enhancing micro-level understanding of the human and emotional side of cross sector partnering. I provide insight on why individuals commit to CSPs and illustrate how this influences behavioural responses to adversity. I also contribute to the commitment literature by shedding light on the interplay of different commitment targets within a cross boundary, socially oriented workplace setting and providing empirical evidence for how altruism facilitates commitment. Finally, I reveal the benefit that sustained commitment generates for partnership practitioners and suggest how my findings may be leveraged for both partnering practice and future research.